(3LGeY GdeHGOF hGdZGjGJ aj Yde GdejbGJs - (3GdMSf Hf Ydj Hf YeQ, CHh Ydj TQa GdOjf GdeQGcTj,J (B660 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg hGdUdGI Ydi eMeO hBdg aEfi QCjJ cKjQkG ef GdfGS jNhVhf ai hVY GdBdGJ GdadcjI hGdfMQjQ efge dGjYQa ef GdMSGH hGdgfOSI s
(3BNQgG (B:s
(3hjJYQa Whd Xd GdYehO GdhGKY ai GdSWM GdeGFd hjSJNQL GdCQJaGY GddGRe dg aeG cGf agh JeGe bOQ ejd GdSWM GdeGFd hGddg Gdehab Je GdbSe GdChd ef Gdaf GdKGfi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B203 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B257s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi s
Keywords: (3Gdadcs